A Low rectal GIST. Issue 3 (14th March 2022) - Connelly, Tara M; Clancy, Cillian; Hu, Shaomin; Steele, Scott R; Kessler, Hermann
Abstract : A man in his 70s presented with narrowing of his stool calibre and a palpable mass on rectal examination. Colonoscopy revealed a submucosal bulge without a mucosal lesion. CT and MRI demonstrated an 8×5.4×7 cm mass in lower rectum. Biopsy of the mass confirmed a rectal gastrointestinal stromal tumour (GIST). It was moderately sensitive to neoadjuvant imatinib and radiotherapy, which slightly downsized the tumour. He required abdominal perineal resection with curative intent. Uncommonly found in the rectum, when located here, GISTs are typically aggressive and are a rare cause of stool calibre narrowing. Rectal GISTs should be considered in patients presenting with this symptom.